Bio-inspired formation of silica particles using the silica-forming peptides found by silica-binding motif sequence, RRSSGGRR. (December 2021) - Min, Ki Ha; Shin, Jin Woo; Ki, Mi-Ran; Kim, Sung Ho; Kim, Kyung Hee; Pack, Seung Pil
Graphical abstract: Highlights: Silica forming peptides were newly found from the search of silica binding motif. The peptide from Winogradskyella arenosi showed better production of silica particles. Biosilica shell-coating of E. coli shows the cyto-protection against UV-C irradiation. Abstract: Silica particles are widely used as versatile materials with applications in catalyst support, biomedical materials, drug delivery systems, coatings, and cosmetics. Silica particle formation by biological catalysts could be more suitable for biotechnological applications. Although silicatein (protein) and R5 (peptide) are well-known as silica-forming biomolecular agents, new biocatalysts which can mediate silica particle synthesis under mild conditions are still needed. Here, we introduced three new silica-forming peptides (SFPs) found by BLASTp search using silica binding motif (RRSSGGRR) as a query. The three peptides were found to mediate biosilica formation under microbial culture conditions at pH 6−7. Among them, the peptide from Winogradskyella arenosi (Wa-RSG) exhibited better performance than other SFPs in the generation of silica particles at pH 6, at which silica is not easily formed. We investigated the optimal amount and reaction time of Wa-RSG for biosilica particle formation at pH 6−7. In addition, we demonstrated that Wa-RSG adsorbed on Escherichia coli cell surfaces could induce silica shell coating of E. coli at pH 6–7, and the biosilica-coated microbes showed stability against harsh UV treatment. These results will be useful for the preparation of bio-integrated silica materials such as biomolecule-containing silica particles or silica-coated industrial microbes.